A role for superficial heat therapy in the management of non-specific, mild-to-moderate low back pain in current clinical practice - Freiwald, Jürgen (2021)
Funding Information: The authors received medical writing support from Niina Nuottamo of Excerpta Medica. The writing support was funded by Angelini Pharma. Funding Information: Acknowledgments: The authors received medical writing support from Niina Nuottamo of Excerpta Medica. The writing support was funded by Angelini Pharma. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.